GENDER DISPARITIES IN SPORTS PARTICIPATION IN INDIA: A SECONDARY DATA ANALYSIS OF SAI ANNUAL REPORTS (2020–2024) - Prince Vishal Dixit and Dr. Munna Kumar Varun (Knowledgeable Research A Multidisciplinary Journal, 2025)
This research paper explores gender-based disparities in sports participation using secondary data drawn from the Sports Authority of India (SAI) Annual Reports from 2020 to 2024. The study evaluates trends in male and female athlete representation across major SAI schemes: National Centers of Excellence (NCOE), SAI Training Centers (STC), Extension Centers, and National Sports Talent Contest (NSTC). Findings reveal consistent underrepresentation of girls, though a gradual improvement is noted in certain schemes. Institutional efforts, such as Khelo India and Fit India initiatives, have contributed positively but gaps persist. Through content and tabular analysis, the study also examines the socio-cultural and structural barriers contributing to this imbalance. The study concludes with recommendations to enhance gender parity in Indian sports.